Deterministic and Probabilistic Health Risk Assessment of Toxic Metals in the Daily Diets of Residents in Industrial Regions of Northern Ningxia, China - Yan Wang; Deyan Cao; Jiaqi Qin; Siyuan Zhao; Jianzai Lin; Xi Zhang; Junji Wang; Meilin Zhu (Biological Trace Element Research, 2023)
This study was designed to investigate the toxic metal (aluminum (Al), arsenic (As), chromium (Cr), cadmium (Cd), copper (Cu), nickel (Ni), lead (Pb), and zinc (Zn)) concentrations in drinking water and different foodstuffs meat (pork, beef, and mutton), cereals (rice, flour, corn, millet), beans (cowpeas, tofu), potatoes (potato, sweet potato), solanaceous fruits (pepper, eggplant, bitter gourd, cucumber), vegetables (cabbage, cauliflower, spinach), and fruits (apples, watermelons, pears, grapes)) and then estimate the potential health risks of toxic metal consumption to local residents in industrial regions of northern Ningxia, China. As in drinking water, Cr in meat, Pb in cereals, Pb in beans, As and Pb in potatoes, Pb in solanaceous fruits, Cr and Ni in vegetables, and Ni and Pb in fruits were the most contaminated heavy metals in the corresponding food with over-standard rates of 16.7%, 12.5%, 5.1%, 60%, 50%, 50%, 38.2%, 44.4%, 44.4%, 31.8%, and 31.8%, respectively. The results of the deterministic assessment of health risks showed that the total noncarcinogenic risk value of dietary intake of toxic metals by the local population was 5.6106, indicating that toxic metals pose a high noncarcinogenic risk. The order of the non-carcinogenic risk is HI cereal (1.2104) > HI solanaceous fruit (0.9134) > HI Vegetables (0.8726) > HI Fruit (0.8170) > HI Meat (0.7269) > HI Drinking water (0.6139) > HI Beans (0.2991) > HI Potatoes (0.1573). The total carcinogenic health risk from exposure to toxic metals through dietary intake was 9.98 × 10 −4 , indicating that the total cancer risk value of residents is beyond the acceptable range (10 −4 ) under the current daily dietary exposure and implies a high risk of cancer. The order of the carcinogenic risk is R Drinking water (2.34 × 10 −4 ) > R Meat (2.11 × 10 −4 ) > R solanaceous fruit (1.89 × 10 −4 ) > R Fruit (1.88 × 10 −4 ) > R cereal (1.36 × 10 −4 ) > R Potatoes (2.44 × 10 −5 ) > R Vegetables (1.51 × 10 −5 ) > R Beans (0). The probabilistic assessment results showed that 98.83% of the population is exposed to severe noncarcinogenic risk and 87.02% is exposed to unacceptable carcinogenic risk. The sensitivity analysis showed that drinking water, local cereals, vegetables, and fruits were the major contributors to health risks. Our results indicated that the daily dietary exposure of residents in industrial regions of northern Ningxia poses a serious threat to human health, and it is suggested that relevant departments should strengthen monitoring and control of the current situation of toxic metal pollution in the environment and continue to pay attention and take measures to reduce the exposure of toxic metals in the diets of residents in this area. Graphical Abstract